Organizational culture in cardiovascular care in Chinese hospitals: a descriptive cross-sectional study. Issue 1 (June 2015) - Yin, Emily; Downing, Nicholas; Li, Xi; Singer, Sara; Curry, Leslie; Li, Jing; Krumholz, Harlan; Jiang, Lixin
Abstract Background Organizational learning, the process by which a group changes its behavior in response to newly acquired knowledge, is critical to outstanding organizational performance. In hospitals, strong organizational learning culture is linked with improved health outcomes for patients. This study characterizes the organizational learning culture of hospitals in China from the perspective of a cardiology service. Methods Using a modified Abbreviated Learning Organization Survey (27 questions), we characterized organizational learning culture in a nationally representative sample of 162 Chinese hospitals, selecting 2 individuals involved with cardiovascular care at each hospital. Responses were analyzed at the hospital level by calculating the average of the two responses to each question. Responses were categorized as positive if they were 5+ on a 7-point scale or 4+ on a 5-point scale. Univariate and multiple regression analyses were used to assess the relationship between selected hospital characteristics and perceptions of organizational learning culture. Results Of the 324 participants invited to take the survey, 316 responded (98 % response rate). Perceptions of organizational learning culture varied among items, among domains, and both among and within hospitals. Overall, the median proportion of positive responses was 82 % (interquartile range = 59 % to 93 %). "Training, " "Performance Monitoring, " and "Leadership that Reinforces Learning" were characterized as the most favorable domains, while "Time for Reflection" was the least favorable. Multiple regression analyses showed that region was the only factor significantly correlated with overall positive response rate. Conclusions This nationally representative survey demonstrated variation in hospital organizational learning culture among hospitals in China. The variation was not substantially explained by hospital characteristics. Organizational learning culture domains with lower positive response rates reveal important areas for improvement.